Will the Economic and Monetary Union in Europe Survive? - Bukowski, Sławomir (Studia Oeconomica Posnaniensia, 2017)
The aim of paper is to answer the question: What conditions should be fulfilled for the survival of the Economic and Monetary Union in the opportunities of symptoms of a financial crisis. The hypothesis concerns sovereign debt repayment and public finance reform in countries with excessive sovereign debt during a financial crisis have been formulated. The results of the analysis indicate that without a reduction of sovereign debt and deep public finance reform on the level of countries and institutional reforms at the EU' level the Economic and Monetary Union will not survive.